The Obligation of Adopted Children to Fulfill Parents' Alimentary Rights - Tjoanda, Merry; Panjaitan, Wijaya Natalia; Lenggono, Roy Prabowo (Batulis Civil Law Review, 2025)
Introduction: Child adoptions have been carried out in different ways and motivations, in accordance with the current legal system and regulations in society. Parents who adopt a child will assume the obligation to raise the adopted child like a biological child. However, the question of the responsibility of the adopted child for the fulfillment of the alimony rights of his or her adoptive parents has also become a legal study and social practice.Purposes of the Research: This research aims to analyze the obligations of adopted children to fulfill their parents' allimentary rights.Methods of the Research: The type of research used is sociolegal research, which is a combination research method between doctrinal legal research methods and empirical legal research methods.Results Main Findings of the Research: Adopted children have clear legal obligations to the adoptive parents in terms of the fulfillment of allimentary rights. In addition, there is a need for clarity to strengthen regulations regarding the rights and obligations of adopted children in the Civil Code in Indonesia. This is important to provide legal certainty for all parties and increase public awareness of the rights and obligations carried by adopted children.